EP310/#1033 Soluble HLA-E and TNF-αlpha expression association in epithelial ovarian carcinoma ascites. (4th December 2022) - Babay, Wafa; Boujelbene, Nadia; Zemni, Ines; Dhouioui, Sabrine; Ayadi, Mohamed Ali; Rebmann, Vera; Zidi, Ines
Abstract : Objectives: Most patients with ovarian carcinoma are diagnosed at an advanced stage, and therapeutic options for these patients still limited. The present study aims to investigate soluble Human leukocyte antigen-E (sHLA-E) and TNF-α inflammatory cytokine expression in ascites of patients with epithelial ovarian carcinoma (EOC). Methods: Thirty ascites specimens from EOC patients were collected. We optimized a direct sandwich enzyme-linked immunosorbent assay (ELISA) method to simultaneously determine the total antibody levels of sHLA-E and TNF-α. Results: Ascites from EOC patients showed increased sHLA-E levels (Mean: 1403pg/m) and TNF-α levels (Mean: 40, 4pg/ml). Interestingly, sHLA-E was positively correlated to TNF-α expression (Spearman r=0.37, p=0.05). Both soluble molecules were decreased in ascites of EOC patients with high CA-125 without significance (CA-125 <35U vs CA125 ≥35U: sHLA-E: 1914 pg/ml vs 1307pg/ml and TNF-a: 154.2pg/ml vs 24.85pg/ml). Conclusions: Our preliminary data demonstrated that sHLA-E and TNF-a are increased in EOC patients' ascites but decreased in those with high CA-125 tumor marker. sHLA-E might be highly secreted to decrease local inflammation and inhibit tumor progression. Further studies could shed light on the potential immune tolerance role of HLA-E in EOC.